Processing of golden snail. - Ignacio, Anna Marie R. (College of Fisheries, University of the Philippines, 1986)
Golden snails were purged, blanched, washed, drained and weighed. They were subjected to different processing and methods of preparation. In the standardization of canning and bottling procedure for golden snails, several trials have been conducted. Golden snails were filled and weighed into 307 x 201.25 C-enameled cans, and processed at 250 degree F for 60 minutes. They were also filled and weighed into an 8 oz bottle, and processed at 250 degree F for 30 minutes. Canned and bottled golden snails, with and without the shells packed in 20% brine solution, which have been standardized, were subjected to thermal resistance study, heat penetration study, and processes calculation. Product quality was measured by organoleptic and chemical parameters. The sensory or organoleptic assessment of the different processed products and fresh samples and percentage yield also determined. Cutout tests were also done on pH, vacuum, gross and net weigh, and headspace. Production cost of the different processed products was post-production work such as distribution and marketing of the products were discussed.